KUALITAS KEPEMIMPINAN, ETOS MORALITAS PRIBADI, KOMPETENSI, DAN PELAYANAN PUBLIK - ', Dody Setyawan; ', Nanang Bagus.S (Jurnal Ilmu Administrasi Negara, 2014)
Ethos Private Morality, Competence, and the Public Service.This study aims to determine the effect of leadership qualities, personal moral ethics, andcompetence in the performance of public services in East Java legislators. The method used isa quantitative method. The study population was a community that metropolis, traditional andcivil society. Sampling was stratified random sampling and purposive sampling with as many as115 respondents. Data collection techniques using koesioner, interviews, and observations. Datawere analyzed with path analysis method with SPSS software. The results showed that the ethosof personal morality and competence indirectly influence on legislators public service throughleadership qualities. To improve the quality of public service leadership legislators in leading thepeople it represents needs to be improved.Keywords: performance, leadership qualities, personal morality ethics, competence, publicservice.